Towards the taxonomy of Corynoneura Winnertz (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East and Eastern Siberia - Makarchenko, Eugenyi A.; Makarchenko, Marina A.; Semenchenko, Alexander A. (Zootaxa, 2019)
The genus Corynoneura Winnertz is partly revised on the basis of materials from the Russian Far East and Eastern Siberia. Adult male of a new species, C. sikhotealinensis sp. nov., as well as pupa of C. schleei Makarchenko et Makarchenko and pupa with associated pharate male of Corynoneura sp. are described. Adult male of C. fujiundecima Sasa, earlier erroneously determined as C. lacustris Edwards, is briefly redescribed and annotated. DNA barcoding results of C. kadalinka Makarchenko et Makarchenko from Eastern Siberia (Baikal Lake basin) are also provided in comparison with closely related C. carriana Edwards from Sweden. As a result of the analysis, supported with sufficiently significant morphological differences between males of these two distant populations, the two species were combined into one, C. carriana, with two subspecies: C. carriana carriana Edwards (nominotypical) and C. carriana kadalinka Makarchenko et Makarchenko stat. nov. A morphological redescriptions of the adult male and pupa, as well as the 4th instar larva (here described for the first time) of C. carriana kadalinka in comparison with specimens of populations of the C. carriana carriana from Sweden and the Urals are presented. A key to adult males and pupae of the Corynoneura species from the Russian Far East and Eastern Siberia is also provided.